Levels of Suicidal Ideations and Intents among the Inmates in the Correctional Institutions in Baghdad City - Iraq - Maan Hameed Ibrahim Al-Ameri (Indian Journal of Forensic Medicine & Toxicology, 2022)
Background: Suicidal ideations concern thinking about suicide or an uncommon and inappropriatepreoccupation with suicide. The range of suicidal ideation and intent differs significantly from briefthoughts to wide thoughts, to comprehensive planning, and role-playing.Objectives: To explore inmates’ levels of suicidal ideation and intent in the prisons of Baghdad Cityand to find out the relationship between these levels and some demographic characteristics of thoseinmates.Methodology: A descriptive analytic design was used to guide this study which was conductedfrom October 15th, 2015 to the June 10th, 2016. A non-probability sample of 100 inmates in Baghdadcorrectional institutions was recruited. The study instrument is a questionnaire consisted of ninedemographic characteristics and 19 items represent Beck suicidal ideations and intents scale. Datawere analysed by using descriptive statistical measures of frequency, percent, and distribution; andinferential analysis (Chi-squire).Results: The study results displayed that more than half of the inmates are from twenties and thirtiesdecades (58.0%), 68.0% having elementary and secondary school, half of them are with six to 15years imprisonment, and 69.0% are married. Three quarters have moderate and high levels of suicidalideations and intents. The study also finds that the more the period of imprisonment and the less ofincome the inmates have the higher the levels of suicidal ideation they have.